2019
DOI: 10.3390/cells8091060
|View full text |Cite
|
Sign up to set email alerts
|

An Autocrine Wnt5a Loop Promotes NF-κB Pathway Activation and Cytokine/Chemokine Secretion in Melanoma

Abstract: Wnt5a signaling has been implicated in the progression of cancer by regulating multiple cellular processes, largely migration and invasion, epithelial-mesenchymal transition (EMT), and metastasis. Since Wnt5a signaling has also been involved in inflammatory processes in infectious and inflammatory diseases, we addressed the role of Wnt5a in regulating NF-κB, a pivotal mediator of inflammatory responses, in the context of cancer. The treatment of melanoma cells with Wnt5a induced phosphorylation of the NF-κB su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 83 publications
2
24
0
Order By: Relevance
“…Using the tumor marker model depicted by Figure 2, this decrease of S100B might be explained by a yet not understood effect of PD-1 blockade on melanoma cell cycle resulting in partial cell cycle arrest and reduced S100B release. It has been observed that melanoma cells may rely on an autocrine secretion of IL-6 [36]. The parallel decrease of IL-6 might indicate that PD-1 blockade interferes with this autocrine IL-6 loop.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the tumor marker model depicted by Figure 2, this decrease of S100B might be explained by a yet not understood effect of PD-1 blockade on melanoma cell cycle resulting in partial cell cycle arrest and reduced S100B release. It has been observed that melanoma cells may rely on an autocrine secretion of IL-6 [36]. The parallel decrease of IL-6 might indicate that PD-1 blockade interferes with this autocrine IL-6 loop.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, two patients in our study demonstrated an immediate and parallel decrease of IL-6 and S100B serum levels after administration of checkpoint inhibitor treatment which might result from a direct suppressive effect of PD-1 blockade on melanoma cell cycle. Under the assumption that IL-6 can be excreted by melanoma cells and may stimulate autocrine growth [36], the parallel decrease of IL-6 in these patients might suggest that blockade of PD-1 did interrupt this putative autocrine loop. High levels of IL-6 secreted by melanoma metastases might mask the IL-6 protein signature deriving from immune activation.…”
Section: Discussionmentioning
confidence: 97%
“…Silencing of BCL2L10 was performed using pLKO.1 shRNA clones TRCN0000033595 and TRCN0000033596 designed by The RNAi Consortium (TRC) and previously validated [ 84 ]. Viral particles were generated as described [ 85 ].…”
Section: Methodsmentioning
confidence: 99%
“…IL6ST (Interleukin-6 receptor subunit beta) is involved in transducing multiple signals, such as IL-6 and IL-11, and might be crucial in severe COVID-19 cases90 . ROR1 (Inactive tyrosine-protein kinase transmembrane receptor ROR1) acts as a receptor, and when activated by WNT5A ligand binding, activates NFB signaling91 . Finally, PTPRJ (Receptor-type tyrosine-protein phosphatase eta; CD148) regulates endothelial cell survival, enhancing epithelial cell junctions as well as VEGF-induced SRC and AKT activation 92 .…”
mentioning
confidence: 99%